The Nlrc4 Inflammasome Contributes to Restriction of Pulmonary Infection by Flagellated Legionella spp. that Trigger Pyroptosis - Pereira, Marcelo S.; Marques, Gabriel G.; DelLama, José E.; Zamboni, Dario S. (Frontiers in Microbiology, 2011)
The Nlrc4 inflammasome is triggered in response to contamination of the host cell cytoplasm with bacterial flagellin, which induces pyroptosis, a form of cell death that accounts for restriction of bacterial infections. Although induction of pyroptosis has been extensively investigated in response to Salmonella typhimurium and Legionella pneumophila, little is known regarding the role of the inflammasome for restriction of non-pneumophila Legionella species. Here, we used five species of the Legionella genus to investigate the importance of the inflammasome for restriction of bacterial infection in vivo. By infecting mice deficient for inflammasome components, we demonstrated that caspase-1 and Nlrc4 contribute to restriction of pulmonary infection with L. micdadei, L. bozemanii, L. gratiana, and L. rubrilucens. Legionella longbeachae, a non-flagellated bacterium that fails to trigger pyroptosis, was not restricted by the inflammasome and induced death in the infected mice. In contrast to L. longbeachae, flagellin mutants of L. pneumophila did not induce mice death; therefore, besides bypassing the Nlrc4 inflammasome, L. longbeachae may employ additional virulence strategies to replicate in mammalian hosts. Collectively, our data indicate that the Nlrc4 inflammasome plays an important role in host protection against opportunistic pathogenic bacteria that express flagellin.